Ureteral stent removal using an extraction string after uncomplicated ureteroscopy: a cost-benefit analysis - Liu, Hao; Pan, Weiyun; Zhang, Nan (Urology Journal, 2018)
Purpose: Some urologists used the extraction strings for removal of ureteral stent without cystoscopy. While some urologists may have concern about perceived risks, including accidental dislodgement, infection, renal?colic?and lower urinary tract symptoms. Therefore, we performed a retrospective study to help address this conflict. Materials and Methods: Patients who had an indwelling ureteral stent with(n=58) or without(n=82) extraction strings inserted after ureteroscopy for unilateral ureteral stones were enrolled. For ureteral stent removal, the strings were pulled by physician, no string-stents were removed by cystoscopic. Postoperative morbidity was assessed. Patients’ medical expense due to postoperative morbidity was collected. Results: Patients with extraction string had shorter stent dwell time((5.3±1.8 versus 11.2±3.2 day, P= .001) and less cost (8.97±3.07 versus 455±0 CNY, P = .001)) for ureteral stent removal. However, six patients with extraction string had an accidental dislodgement, additional medical expenses were 345±137.9 CNY. There was no difference in the cost due to urinary tract infection, renal?colic?and LUTS between the two groups. The overall cost in patients without an extraction string was significantly more than in patients with an extraction string (86.7±167.7 versus 507.9±147.8 CNY, p =.008). Conclusion: Despite an increase in stent dislodgement related risks to the extraction string, it results in significant cost savings for patients, and most of patients remove with extraction strings might benefit from it. INTRODUCTION Nowadays, most of urologists place an indwelling ureteral stent following uncomplicated ureteroscopy(URS). However, ureteral stent may impact quality of life (QoL) of patients. And the additional suffering due to cystoscopic extraction is even more painful. Current ureteral stents are manufactured with a string attached to the distal end, allowing for removal without cystoscopy, which may lead to a reduction of the dwell time(usually less than one week)[1-8]. Although stent extraction strings have many advantages, more than two-thirds of urologists remove extraction strings prior to their insertion[9]. Surgeons who do not adopt?this?method?may have concern about perceived risks, including accidental dislodgement, infection, renal?colic?and lower urinary tract symptoms(LUTS). But how about incidence?rate of the risk aforementioned??does this increase the patient’s financial burden compared with patients remove without extraction strings? Whether patients remove with extraction strings might benefit from it? Therefore, we performed a retrospective study to help address these questions by comparing patients those who underwent ureteric stent placement with and without extraction strings after URS for stone disease.